2018
DOI: 10.1016/j.rmed.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil added to pirfenidone in patients with advanced idiopathic pulmonary fibrosis and risk of pulmonary hypertension: A Phase IIb, randomised, double-blind, placebo-controlled study – Rationale and study design

Abstract: Combination treatment with sildenafil and pirfenidone may warrant investigation of the treatment of patients with advanced IPF and pulmonary vascular involvement leading to PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 53 publications
1
23
0
1
Order By: Relevance
“…Pulmonary hypertension frequently complicates severe fibrosis and is associated with diminished survival in IPF patients [84,85]. Multiple clinical trials of monotherapies with PAH drugs targeting either pulmonary hypertension-IPF or IPF have yielded negative results [84][85][86][87][88]. However, a subgroup analysis of the STEP-IPF (Sildenafil Trial of Exercise Performance in Idiopathic Pulmonary Fibrosis) trial of sildenafil, a phosphodiesterase-5 inhibitor, reported some positive secondary outcomes including improvements in oxygenation, DLCO and, especially, HRQL [86].…”
Section: Combination Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary hypertension frequently complicates severe fibrosis and is associated with diminished survival in IPF patients [84,85]. Multiple clinical trials of monotherapies with PAH drugs targeting either pulmonary hypertension-IPF or IPF have yielded negative results [84][85][86][87][88]. However, a subgroup analysis of the STEP-IPF (Sildenafil Trial of Exercise Performance in Idiopathic Pulmonary Fibrosis) trial of sildenafil, a phosphodiesterase-5 inhibitor, reported some positive secondary outcomes including improvements in oxygenation, DLCO and, especially, HRQL [86].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Subgroup analyses are still pending. An ongoing phase IIb trial (NCT02951429) currently examines the effect of combined sildenafil and pirfenidone therapy in patients with advanced IPF and risk of pulmonary hypertension [88].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…However, Nawata et al [53] Table 2 and the results of the estimation are given in Table 3. The estimate of BP_medicine is 5.1 mmHg for Model 1 and the t-value is 34.82. Although the values are smaller (about half) those of the previous section, this means that the SBP of individuals with BP medicines are still higher than those without even when controlling for various individual factors.…”
Section: Regression Analysis Using Bp_medicine Dummymentioning
confidence: 98%
“…Double-blind RCT, where both participants and researchers are unaware as to who is receiving prescribed medicines, are usually used. Numerous studies on treatments for hypertension and related diseases have been conducted by double-blind RCT [21]- [34]. However, ethical problems with double-blind RCT have also been widely discussed [35]- [45].…”
Section: Introductionmentioning
confidence: 99%
“…Despite INSTAGE being a negative study (6), this is not necessarily the end for sildenafil in IPF. A phase IIb study comparing the addition of sildenafil or placebo to pirfenidone in IPF patients is ongoing (11). This study will again target patients with advanced disease (D LCO ≤40% predicted), but will also specifically recruit patients who are at risk of pulmonary hypertension secondary to lung disease.…”
mentioning
confidence: 99%